Zingiber officinale and Vernonia amygdalina Infusions Improve Redox Status in Rat Brain. (26th September 2022) - Rotimi, Damilare Emmanuel; Ben-Goru, Goodnews Mavoghenegbero; Evbuomwan, Ikponmwosa Owen; Elebiyo, Tobiloba Christiana; Alorabi, Mohammed; Farasani, Abdullah; Batiha, Gaber El-Saber; Adeyemi, Oluyomi Stephen
Abstract : The study investigated the effects of Zingiber officinale root and Vernonia amygdalina leaf on the brain redox status of Wistar rats. Twenty-four (24) rats weighing 160 ± 20 g were randomly assigned into four (4) groups, each with six (6) rats. Animals in Group 1 (control) were orally administered distilled water (1 mL), while the test groups were orally administered 5 mg/mL of either Z. officinale, V. amygdalina infusion, or a combination of both, respectively, for 7 days. The rats were sacrificed at the end of treatments and blood and tissue were harvested and prepared for biochemical assays. Results showed that administration of V. amygdalina and Z. officinale, as well as their coadministration, reduced the levels of malondialdehyde (MDA), nitric oxide (NO), acetylcholinesterase (AChE), and myeloperoxidase (MPO) in rat brain tissue compared with the control group. Conversely, coadministration of V. amygdalina and Z. officinale increased the levels of reduced glutathione (GSH) in rat brain tissue compared with the control group. However, the administration of the infusions singly, as well as the combination of both infusions, did not have any effect on the rat brain levels of glutathione peroxidase (GPx) and catalase (CAT) antioxidant enzymes compared to the control. Taken together, the findings indicate that the V. amygdalina and Z. officinale tea infusions have favorable antioxidant properties in the rat brain. The findings are confirmatory and contribute to deepening our understanding of the health-promoting effects of V. amygdalina and Z. officinale tea infusions.